(untitled) (Encuentros, 2023)
The adoption of automated marketing communications through a CRM platform in a Colombian SME is presented. Bitrix24 is a software for business workflow automation. This case study was carried out through the observation of the implementation of this platform in the company. In addition, in-depth interviews with the manager, specialists from the marketing areas and sessions with the expert trainer of Bitrix24. The results show that an SME can transfer a large part of the marketing communication strategies to an automated platform, saving time and costs in its implementation; however, trained personnel and a conception of digital transformation are required at all levels of the organization.